The Strategy of Minimizing Safety Incidents and Implementing Risk Management to Overcome Crew Error (Human Error) on PT. Meratus Line Surabaya - Caesar Richardo Bintang Samudra Tampubolon; Suprihono Setyawan (International Journal of Management, Business, and Social Sciences, 2026)
This study aims to describe the efforts of PT. Meratus Line Surabaya in minimizing the risk of human error among ship crew members. The research employed a qualitative approach with managers, staff, and crew as the subjects. Data were collected through observation, interviews, and documentation, and then analyzed descriptively. The findings indicate that risk prevention is carried out through the selection and placement of crew according to their qualifications, skill enhancement through training, and the provision of personal protective equipment. The strategies implemented include workplace orientation, familiarization, and continuous training to create a safe working environment. The challenges encountered involve unauthorized task execution, improper use of personal protective equipment, and lack of discipline. The solutions applied consist of direct supervision, regular inspections, and guidance through training. This study highlights the importance of a systematic approach in managing human error risks in the maritime sector.